Penyuluhan Etika Bermedia Sosial Berbasis Hukum Dan Ajaran Islam Untuk Pencegahan Cyberbullying Pelajar SMK Ma’arif Sukaslamet - Fitria Insani; Nahlia Puteri Madini; Shofi Eka Romandhoni; Fuad Arrasyid Almubarok; Muhammad Isa Asyrofuddin (Universitas Negeri Gorontalo, 2026)
Cyberbullying is a form of digital violence that has become increasingly prevalent among students along with the high intensity of social media use, which is not yet balanced by adequate ethical awareness, legal literacy, and internalization of moral values. This condition highlights the need for preventive efforts through a comprehensive educational approach. This Community Service activity aims to enhance students’ understanding and awareness of cyberbullying prevention by integrating a positive legal approach and Islamic values. The method employed was a one-cycle participatory educational intervention design involving 30 students of SMK Ma’arif Sukaslamet, Indramayu Regency, implemented through three stages: preparation, implementation, and evaluation. The educational materials covered the concept and forms of cyberbullying, its psychosocial impacts, the provisions of Article 27A of Law Number 1 of 2024 on Electronic Information and Transactions, and the interpretation of Qur’an Surah Al-Hujurat verse 11 as an ethical foundation for social media use. The results indicate an improvement in participants’ understanding, as reflected in their ability to identify cyberbullying behaviors, explain their legal consequences, and relate social media practices to Islamic ethical values. These findings suggest that an educational approach integrating positive law and Islamic teachings contributes positively to fostering more ethical, responsible, and respectful digital behavior among students.